Preliminary corrosion prevention of microbiologically induced corrosion in high producer main oil pipelines to hinder reoccurrence leak - Michael Oktavianes Pamula; Vitus Denny; Haryo Rahmadani; Marannu Arham; Andika Amanatillah; Taufik Aditiyawarman; Agus Paul Setiawan Kaban (Results in Engineering, 2024)
Microbiologically induced corrosion (MIC) is a prominent issue in high-producer main oil lines (MOL) despite the stringent mechanical and chemical treatment due to Sulfate-reducing bacteria (SRB). Monthly corrosion monitoring shows the number of bacteria on the pig body and in seawater remains significant. The investigation corresponds with the dormancy and duplication of SRB retains in siloes due to uncontrolled parameters such as injection schedule and the ideal biocide dosage. While investigating and predicting the resistant bacteria that may threaten the pipeline is an attractive discussion, modelling the corrosion mitigation using a corrosion test is equally essential to predict the effectiveness of biocides. Biocide performance was evaluated in a few test solutions from two locations in one of the well-established oil company producers in northwest Java. The corresponding time-kill test using Tetrakis (hydroxymethyl) Phosphonium Sulfate (THPS) adheres to NACE TM- 0194 (2014) standard to obtain the optimum biocide dosing of the bacteria solution. Biofilm and micro-pitting were identified by evaluating the blank and 1000 μg/L 60% THPS solutions using a Scanning Electronic Microscope (SEM). Based on the time kill test, the inactive bacteria in dormancy after injection 500 μg/L and 1000 μg/L THPS 60%. The wheel corrosion test shows ineffective injection increases chemical acidity and corrosion rate. The SEM result confirms the time-kill test and indicates the possible sessile bacteria and biotic pitting. This work exemplifies the comprehensive engagement between the field operation and experimental work to quicken the MIC analysis and recommend a viable strategy for the parameter field variation.